Evaluation and management of sports-related eye injuries - Toldi, J. P.; Thomas, J. L. (Current Sports Medicine Reports, 2020)
Ocular injuries occur at a high rate in the United States and are a common complaint in the emergency department (ED). The CDC estimates that the annual rate for all-cause ocular injuries presenting to the ED is approximately 37.6 per 10,000 (1). The personal impact of ocular injury is an obvious one which necessitates urgent evaluation and possibly emergent ophthalmologic evaluation for vision preserving intervention. Specific sports and recreational activities increase the risk of injury; these include sports involving projectiles (i.e., target shooting, racquet sports, hockey pucks, lacrosse) as well as combat sports (i.e., martial arts, boxing, wrestling). Sideline physicians should be aware of the sports setting and be prepared for ocular injuries with the proper sideline equipment. Prompt recognition, management, and referral can lead to decreased morbidity in this select population.